Problematika Membaca Teks Bahasa Arab pada Siswa Sekolah Menengah: Faktor Penyebab dan Upaya Mengatasinya - Hafiluddin, Annisa; Irfan; Al Ilmullah, Syarifah Fathimah (Program Studi Pendidikan Bahasa Arab, 2026)
The ability to read Arabic texts is a fundamental competency in Arabic language learning and in understanding Islamic sources. However, students in Islamic-based general secondary schools, particularly senior high schools, continue to face complex reading difficulties that have not been extensively explored. This study aims to describe the problems in Arabic text reading skills, their causal factors, and the efforts to overcome them among eleventh-grade students at Muhammadiyah Pinrang Senior High School. This study employed a qualitative descriptive approach using a case study design. The research participants consisted of 16 eleventh-grade students, with supporting informants including the Arabic language teacher, the vice principal for curriculum affairs, and the principal. Data were collected through observation, interviews, and documentation. The findings revealed that the linguistic problems included difficulties in recognizing Hijaiyyah letters, pronunciation errors, limited vocabulary mastery, and difficulties in understanding reading texts. Meanwhile, the non-linguistic problems included shyness and lack of self-confidence when reading, lack of focus and attention, and low participation in reading activities. Internal factors included low learning motivation, poor reading habits, and differences in students’ basic reading abilities. External factors included the teacher’s educational background not being in Arabic language studies, limited instructional time, inadequate learning facilities, and the ineffective implementation of the Arabic language habituation program. This study recommends integrated interventions, including reactivating the Arabic language habituation program, providing textbooks, conducting gradual reading exercises to strengthen mastery of Hijaiyyah letters and makhraj, implementing peer tutoring, enhancing students’ vocabulary mastery, and providing motivation and support. The study contributes to the understanding of Arabic reading problems in the senior high school context, which differs structurally from madrasah aliyah, and proposes pedagogical, psychological, and institutional intervention frameworks.